Development of the idea of forming health culture of a person in the world educational thought - T.S. Iermakova (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose - to reveal the basic ideas of pedagogues and scholars of the past regarding the issue of forming health culture of the younger generation. Material : 22 analyzed literary sources on the issue of formation of physical culture and development of healthy individual. Results. The desire to know the laws of nature, man, to the development of philosophy was a characteristic of the Renaissance period. Ideas recreation areas within the educational system were reflected in the writings of the New Age pedagogues and so-called neo-classical period, which was justified by the need to care about their own health and the mastery of the means of achieving health. Pedagogues were justified wellness ideas within the education of the person. Physical education is defined as a basis for the development of a healthy personality. Conclusions. The problem of formation of physically and mentally healthy personality arose with the emergence of human society and formed, supplemented, reinvents for centuries.